Scientific schools and directions of economic theory on the modern era of development - S. S. Repin; L. V. Gogolina (Путеводитель предпринимателя, 2021)
The modern expansion of subject areas of application in the development of economic theory, scientists, as a rule, distinguish four large eras of development, which are equal in their level of influence on the development of economic knowledge.